THE CHARACTER DISCOURSE OF MINANGKABAU CULTURE (MATRILINEAL) IN GUS TF SAKAI'S NOVEL AND SHORT STORIES - Fadlillah Fadlillah (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Matrilineal Minangkabau culture are in marginalized and subjected to violent attacks in the vortex of globalization epistemic capitalistic culture. Thus, the principal issue is how the matrilineal Minangkabau culture character discourse in the target epistemic violence in the literary works of Gus tf Sakai. The violence is at the facts that are not able to disclosed historical, social and political over the years, but it is only disclosed literature. One is the issue of humanitarian discourse on culture. Literature is a cultural issue to be explored, dismantled and examined; about